Effect of a different caeruloplasmin assay method on the relationship between serum copper and caeruloplasmin. Issue 996 (18th November 2008) - Twomey, P J
Abstract : Background: The assessment of copper status is difficult. When investigating excess and deficient copper states, healthcare professionals usually assume that the locally available caeruloplasmin and copper assay results are comparable to data from the literature. Objective: To investigate the effect of different caeruloplasmin assays on the relationship between copper and caeruloplasmin. Methods: Caeruloplasmin and copper results were obtained retrospectively from the laboratory information system before and after a change in the caeruloplasmin assay method. The central tendencies and population confidence intervals for copper and caeruloplasmin were compared. Linear regression analysis was carried out to determine the exact relationship (slope and intercept) between caeruloplasmin and copper. The graph of copper versus caeruloplasmin was also examined to see if the confidence intervals overlapped or not. Finally, the χ 2 test was used to determine if there was a difference with respect to the lower reference intervals for the caeruloplasmin assays. Results: There were 338 and 461 patients in the first and second methods, respectively. None of the patients had Wilson disease. There was no difference between the central tendency copper concentrations or the 95% confidence intervals for the population copper concentrations for the two periods. However, there were differences between the two caeruloplasmin assay methods for both the central tendencies and the population confidence intervals. The data show a statistically significant difference in the relationship between caeruloplasmin and copper associated with the change in the caeruloplasmin assay. There were seven and 100 patients with caeruloplasmin concentrations <200 mg/l with the first and second methods, respectively, which was a significant difference (χ 2 test; p<<0.001). Conclusions: This study shows that that the relationship between copper and caeruloplasmin depends on the caeruloplasmin assay used. A caeruloplasmin assay that reads too high may miss cases of Wilson disease (false negatives), and an assay that reads too low (false positives) may result in further investigations to exclude Wilson disease. Assay-based cut-offs are essential for the investigation of copper excess and deficiency states in the absence of proper assay standardisation. Each laboratory should verify their caeruloplasmin assay reference interval to avoid false positives and/or false negative results.